Prospective Science Teachers Perception of Local Resources based Curriculum for Learning Science Concepts - Latip, Abdul; Park, Do-Yong; Kadarohman*, Asep; Hernani, Hernani; Anggriawan, Robby (Universitas Syiah Kuala, 2025)
A community-based curriculum emphasizes the utilization of local community resources to enrich science learning. Garut, situated in west Indonesia, boasts abundant local resources that can serve as valuable curricular materials for science instruction. This study delves into the perceptions of secondary prospective science teachers regarding the local community resources vis–vis science concepts. Thirty-four aspiring secondary science educators from a university in Garut participated in the investigation. The locale features several noteworthy resources, including the Kamojang geothermal field, the leather tanning industry, and Garut sheep. Data collection involved surveys and interviews, with analysis conducted through descriptive statistics and constant comparative methods. Overall, prospective teachers exhibited awareness of Garut's three primary local resourcesnamely, the Kamojang geothermal field (70.6%), the leather tanning industry (88.2%), and Garut sheep (67.6%). However, they lacked direct engagement with these resources, whether through site visits, ownership, maintenance, or comprehensive knowledge of their developmental processes. Furthermore, participants displayed varying levels of understanding regarding concepts related to geothermal science (31.63%), Garut sheep (52%), and the leather tanning industry (24.6%). Interviews depicted a growing inclination toward leveraging local resources in future science instruction. The findings underscore the imperative for prospective teachers to enhance their understanding of science concepts linked to each of Garut's community resources